THE VIRTUOUS EMOTIONS OF EURIPIDES' MEDEA. (April 2021) - Allan, William
Abstract : The topic of 'virtuous emotions' might not seem the most obvious choice for a play featuring an unfaithful husband and a child-killing mother. Nonetheless, what I intend to consider here is how the emotional responses of various characters in the Medea shape our view of their moral character. The moral role of the emotions was clear to the ancient Greeks and, after a long interlude largely dominated by the idea that, as Kant claimed in The Metaphysics of Morals, 'no moral principle is based…on any feeling whatsoever', moral philosophy of the past half-century or so has returned to seeing the emotions as a central part of human experience and ethical evaluation.